2018
DOI: 10.1177/1557988318754915
|View full text |Cite
|
Sign up to set email alerts
|

Social Support for Exercise as a Predictor of Weight and Physical Activity Status Among Puerto Rican and Mexican Men: Results From the Latino Men’s Health Initiative

Abstract: Social support is an important factor in increasing positive health outcomes and positive health behaviors across a variety of disease states including obesity. However, research examining the relationship between social support for exercise and weight and physical activity status, particularly among Latino men, is lacking. This paper examined whether social support for exercise predicted weight and physical activity status and whether the direction of these relationships differ as a function of Hispanic/Latin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
3
0
2
Order By: Relevance
“…In accordance with previous research (Craven et al, 2018;Duncan & McAuley, 1993), inadequacy perceptions therefore may be a contributing factor as to why inactive individuals need social support from their peers in order to engage with physical activity. Theoretical understandings of this phenomenon lend to conceptualisations from the social cognitive theory (Bandura, 1986).…”
Section: Theme 3: Psychosocial Influence Of Smartphone Precedence Ovesupporting
confidence: 87%
“…In accordance with previous research (Craven et al, 2018;Duncan & McAuley, 1993), inadequacy perceptions therefore may be a contributing factor as to why inactive individuals need social support from their peers in order to engage with physical activity. Theoretical understandings of this phenomenon lend to conceptualisations from the social cognitive theory (Bandura, 1986).…”
Section: Theme 3: Psychosocial Influence Of Smartphone Precedence Ovesupporting
confidence: 87%
“…This is the first known study to assess the validity and reliability of the Spanish-language version of the Social Support for Exercise Scale despite its common use in previous studies (Craven et al, 2018;Hartman et al, 2011;Keller et al, 2014;Marcus et al, 2016;B. Marquez et al, 2016;D.…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish-language version has been used by researchers examining social support among Spanish-speaking samples (Craven, Keefer, Rademaker, Dykema-Engblade, & Sanchez-Johnsen, 2018;Hartman et al, 2011;Keller et al, 2014;Marcus et al, 2016;B. Marquez, Dunsiger, Pekmezi, Larsen, & Marcus, 2016;D.…”
Section: Introductionmentioning
confidence: 99%
“…The same study noted that the stark differences in the role of acculturation in dietary intake, physical activity, smoking/alcohol consumption and obesity are largely the result of differences among Latino subgroups. In a study examining social support and exercise, it was found that research gaps remain to improve understanding of how healthcare outcomes and socioeconomic factors differ in Puerto Rican and Mexican Latino subgroups (Craven et al, 2018).…”
Section: Online Journal Ofmentioning
confidence: 99%